Endobronchial hamartoma; a rare structural cause of chronic cough - Ahmed, Saman (Respir Med Case Rep, 2017)
Pulmonary hamartomas are rare benign tumors consisting of multiple mesenchymal cell lines like cartilage, bone and fat. We discuss an interesting case of a 53-year-old male patient, who was referred to our clinic for persistent cough. Chest X-ray revealed a left suprahilar density associated with plate like atelectasis, which on chest CT was found to be a densely calcified nodule, causing narrowing of the left upper lobe (LUL) bronchus with calcified bilateral hilar lymph nodes. A bronchoscopy revealed a smooth endobronchial mass with calcification, which was removed. Histopathology revealed pulmonary hamartoma.